Detection of Gas Inflow during the Onset of a Starburst in a Low-mass Galaxy at z = 2.45 - Erin Coleman; Keerthi Vasan G.C.; Yuguang Chen; Tucker Jones; Sunny Rhoades; Richard Ellis; Dan Stark; Nicha Leethochawalit; Ryan Sanders; Kris Mortensen; Karl Glazebrook; Glenn G. Kacprzak (The Astrophysical Journal Letters)
The baryon cycle is crucial for understanding galaxy formation, as gas inflows and outflows vary throughout a galaxy’s lifetime and affect its star formation rate. Despite the necessity of accretion for galaxy growth at high redshifts, direct observations of inflowing gas have proven elusive, especially at z  ≳ 2. We present a spectroscopic analysis of a galaxy at redshift z = 2.45, which exhibits signs of inflow in several ultraviolet interstellar absorption lines, with no clear outflow signatures. The absorption lines are redshifted by ∼250 km s ^−1 with respect to the systemic redshift, and C iv shows a prominent inverse P-Cygni profile. Simple stellar population models suggest that this galaxy has a low metallicity (∼5% solar), with a very young starburst of age ∼4 Myr dominating the ultraviolet luminosity. The gas inflow velocity and nebular velocity dispersion suggest an approximate halo mass of order ∼10 ^11 M _⊙ , a regime in which simulations predict that bursty star formation is common at this redshift. We conclude that this system is likely in the beginning of a cycle of bursty star formation, where inflow and star formation rates are high, but where supernovae and other feedback processes have not yet launched strong outflows. In this scenario, we expect the inflow-dominated phase to be observable (e.g., with net redshifted interstellar medium absorption) for only a short timescale after a starburst onset. This result represents a promising avenue for probing the full baryon cycle, including inflows, during the formative phases of low-mass galaxies at high redshifts.